Cyclic topology enhances the killing activity of polycations against planktonic and biofilm bacteria. Issue 25 (10th March 2022) - Wu, Bin; You, Wei; Wang, Hai-Li; Zhang, Ze; Nie, Xuan; Wang, Fei; You, Ye-Zi
Abstract : We showed the enhanced killing activity of cyclic polycation against planktonic bacteria due to higher local charge density and enhanced bactericidal effect in biofilm owing to smaller hydrodynamic volume than linear analogues. Abstract : Bacterial biofilms, as a fortress to protect bacteria, enhance resistance to antibiotics because of their limited penetration, which has become a major threat to current anti-infective therapy. Antimicrobial polycations have received wide attention to kill planktonic bacteria because of their unique antimicrobial mechanism without drug resistance but it is still hard to kill the bacteria in the deep of the biofilm. Unlike linear polymers, the cyclic topology has been demonstrated with enhanced penetration in tissues, which is attributed to the lack of end groups, constrained conformation and a smaller hydrodynamic volume, opening a new sight of polycations in the antibacterial application against biofilms. Here, polycations with different topologies including linear and cyclic polycations were synthesized and their killing activity against planktonic and biofilm bacteria was studied. The experimental results showed the enhanced antibacterial activity of cyclic polycations for planktonic bacteria, which is presumably attributed to their smaller hydrodynamic volume, higher local density of positive charge and more interactions between cation units and the bacterial membrane than their linear analogues. Besides, cyclic polycations exhibit enhanced killing effect for biofilm bacteria and inhibition effect for biofilms with 5–7 times and 2–3 times enhancements than the linear polycations, respectively. Furthermore, an Escherichia coli infection model on mice was established and the therapeutic effects of cyclic and linear polycations were evaluated. Compared with the linear polycations, the cyclic polycations exhibited enhanced antibacterial activity with an ∼4 times increase, promoting the healing of the infected wounds. This work provides a new perspective in the development of antimicrobial polycations, which are promising therapeutic agents to kill planktonic and biofilm bacteria without drug resistance.